Evaluación de la sustitución parcial de la malta de cebada (Hordeum vulgare) por maíz malteado (Zea mays) con adición de mucílago de cacao (Theobroma cacao L.) en cerveza artesanal tipo ale. - Guerrero Morante, Romyna Samantha (2024)
The objective of this study was to evaluate the effects of the partial substitution of barley malt by malted corn and the addition of cocoa mucilage on the physicochemical, sensory and microbiological properties of a craft ale beer. A completely randomized experimental design with five treatments was applied, evaluating the physicochemical, sensory and microbiological parameters of the resulting beers. In addition, the production cost of these beers was estimated, producing 36 bottles of 330 mL each, at a cost of $789.88, which implies a cost of $21.94 per bottle, and an income of $108 USD, resulting in a loss margin of -86.32 %. According to Pearson's correlation, the alternative hypothesis that the partial substitution of barley malt with malted corn and the addition of cocoa mucilage affects the physicochemical properties of ale beer is accepted, showing a negative correlation between acidity and pH, and a positive correlation between acidity and alcoholic strength, as well as between pH and alcoholic strength. This indicates that the higher the acidity, the lower the pH and the higher the alcohol content. T1 (Barley 1000 g, hops 6 g, yeast 4.6 g and mucilage 8 g) obtained higher acceptability, with six respondents expressing positively the acceptability of the beer. Further experiments substituting other grains are recommended.